Perspective on Turing paradigm: An essay - Trzęsicki, Kazimierz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
Scientific knowledge is acquired according to some paradigm. Galileo wrote that the “book of nature” was written in mathematical language and could not be understood unless one first understood the language and recognized the characters with which it was written. It is argued that Turing planted the seeds of a new paradigm. According to the Turing Paradigm, the “book of nature” is written in algorithmic language, and science aims to learn how the algorithms change the physical, social, and human universe. Some sources of the Turing Paradigm are pointed out, and a few examples of the application of the Turing Paradigm are discussed.
Keywords: Galileo Galilei; Alan Turing; Konrad Zuse; zero; Arabic numeral; paradigm; mathematics; algorithmics